Formation of hybrid carriers based on albumin and polyoxometalate for targeted drug delivery - M.O. Tonkushina; I.D. Gagarin; V.R. Gavrilyuk; K.A. Piunov; A.A. Ostroushko (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
The use of proteins to create the targeted drug delivery systems is a promising approach in medicine and has many advantages. The formation of hybrid drug carriers based on proteins and polyoxometalates has a number of additional benefits. Polyoxometalates are able to bind both proteins and molecules of certain drugs to obtain water-soluble products without the use of toxic reagents and organic solvents. The regulation of the experimental conditions allows to control the size of the particles formed in solution. The gradual destruction of polyoxometalate Mo72Fe30 at blood pH provides a pH-dependent mechanism for drug release from the carrier structure. In our research, we obtained bovine serum albumin associated with coordination complexes Mo72Fe30-doxorubicin and Mo72Fe30-tetracycline in aqueous solution. A decrease in the rate of the drug release in a phosphate buffer solution at pH 7.4 (blood pH) from the obtained materials compared to systems not containing albumin was observed. The data obtained in this study shed light on the formation patterns of multicomponent supramolecular systems, consisting of polyoxometalates, proteins, and drugs. The results indicate the possibility of creating hybrid carriers for targeted drug delivery based on polyoxometalates and albumin using non-covalent binding.